Parotid pleomorphic adenomas: Factors influencing surgical techniques, morbidity, and long-term outcome relative to the new ESGS classification in a retrospective study - Schapher, Mirco; Koch, Michael; Agaimy, Abbas; Goncalves, Miguel; Mantsopoulos, Konstantinos; Iro, Heinrich (Journal of Cranio-Maxillofacial Surgery, 2019)
Purpose: To assess long-term results after treatment of parotid pleomorphic adenomas (PPAs) with different surgical techniques, standardized according to the European Salivary Gland Society (ESGS) classification system. Methods: We analyzed ESGS categories, occurrence of facial nerve paresis (FNP), Frey's syndrome, histopathology, and recurrences. Surgical modalities were compared, differentiating techniques with and without facial nerve dissection. A strict protocol ensured a postoperative follow-up-period of more than 7 years. Results: 205 patients were included. A complete follow-up was possible in 138 patients, 77 of whom underwent extracapsular dissection (ED) and 61 of whom had other surgical modalities (OSMs). ESGS categories correlated with the extent of surgery, significantly with the risk for FNP and Frey's syndrome, but not with recurrences. Recurrences did not differ significantly between ED and OSMs, whereas the risks for FNP (p < 0.001 each) and Frey's syndrome (p = 0.000) were significantly higher after OSMs in comparison with ED. Young women with a stroma-rich (myxoid) tumor subtype appear to have the greatest risk for recurrences. Conclusion: ED is the treatment of choice for PPAs, if possible, resulting in similar recurrence rates but significantly fewer comorbidities in comparison with more extensive surgery. After the treatment of PPAs, a long-term follow-up is needed, including imaging.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Extracapsular dissection; Facial nerve paresis; Follow-up; Frey's syndrome; Pleomorphic adenoma; Recurrence